Infrared-emitting, peptidase-resistant fluorescent ligands of the bradykinin B2 receptor: application to cytofluorometry and imaging. (December 2016) - Gera, Lajos; Charest-Morin, Xavier; Jean, Melissa; Bachelard, Hélène; Marceau, François
Abstract Background We have previously reported the design, pharmacological properties and imaging application of bradykinin (BK) B2 receptor (B2 R) ligands conjugated with fluorophores such as fluorescein derivatives at their N-terminus. To take advantage of the high penetration of infrared light into living tissues and their low autofluorescence in this region of the spectrum, additional probes conjugated with cyanine dye 7 (Cy7) were synthesized and characterized. Results The antagonist B-9430 (D-Arg-[Hyp3, Igl5, D-Igl7, Oic8 ]-BK) and the agonist B-9972 (D-Arg-[Hyp3, Igl5, Oic7, Igl8 ]-BK) were N-terminally extended with the infrared fluorophore Cy7, producing the peptides B-10665 and B-10666, respectively. Pharmacological studies indicated that the agonist B-10666 lost much affinity for the B2 R vs. the parent peptide, whereas the antagonist B-10665 better retained its potency vs. B-9430 (competition of [3 H]BK binding to human B2 R, contractility of the human isolated umbilical vein for which potency losses were more important in each case). Both probes stained HEK 293 cells that expressed the B2 R-green fluorescent protein (GFP) construction in a specific manner (confocal microscopy) and with very extensive co-localization of the green and infrared fluorescence in either case. The agonist B-10666 at 100 nM promoted the endocytosis of B2 R-GFP in live cells, but not the antagonist version at 10–25 nM. The Cy7-labeled peptides did not label cells expressing the β2 -adrenoceptor-GFP construction. B-10665 at low nanomolar concentrations was an effective probe for the recombinant B2 Rs in cytofluorometry and macroscopic imaging of cell wells (IVIS imaging system operated for infrared fluorescence detection). Conclusions Despite a propensity for non-specific binding when used at high concentrations and limited sensitivity, Cy7-conjugated peptidase-resistant B2 R ligands support original imaging and cytofluorometric applications.